Evaluation of Galcanezumab for the Prevention of Episodic Migraine: The EVOLVE-1 Randomized Clinical Trial - Stauffer, Virginia L; Dodick, David W; Zhang, Qi; Carter, Jeffrey N; Ailani, Jessica; Conley, Robert R (JAMA neurology, 2018)
Migraine is a disabling neurological disease characterized by severe headache attacks. Treatment options reduce migraine frequency for many patients, but adverse effects lead to discontinuation in many patients. To demonstrate that galcanezumab is superior to placebo in the prevention of episodic migraine with or without aura. The EVOLVE-1 (Evaluation of LY2951742 in the Prevention of Episodic Migraine 1) trial was a double-blind, randomized, placebo-controlled (January 11, 2016, to March 22, 2017) trial comparing galcanezumab (120 mg and 240 mg) vs placebo. Patients received treatments once monthly for 6 months (subcutaneous injection via prefilled syringe) and were followed up for 5 months after their last injection. It was a multicenter, clinic-based study involving 90 sites in North America. Participants in the study were adults (aged 18 to 65 years) with at least a 1-year history of migraine, 4 to 14 migraine headache days per month and a mean of at least 2 migraine attacks per month within the past 3 months, and were diagnosed prior to age 50 years. During the study, no other preventive medications were allowed. A total of 1671 patients were assessed; 809 did not meet study entry or baseline criteria, and 858 were included in the intent-to-treat population. Patients were randomized (2:1:1) to monthly placebo, galcanezumab, 120 mg, and galcanezumab, 240 mg. The primary outcome was overall mean change from baseline in the number of monthly migraine headache days during the treatment period. Secondary measures included at least 50%, at least 75%, and 100% reduction in monthly migraine headache days, migraine headache days with acute medication use, and scores from the Migraine-Specific Quality of Life questionnaire, Patient Global Impression of Severity, and Migraine Disability Assessment. Treatment-emergent adverse events and serious adverse events were reported. Of the 1671 patients assessed, 858 (mean age, 40.7 years; 718 women [83.7%]) met study entry criteria and received at least 1 dose of investigational product. The primary objective was met for both galcanezumab doses; treatment with galcanezumab significantly reduced monthly migraine headache days (both P < .001) by 4.7 days (120 mg) and 4.6 days (240 mg) compared with placebo (2.8 days). All key secondary objectives were also significant after multiplicity adjustment. There were no meaningful differences between 120-mg and 240-mg doses of galcanezumab on measures of efficacy. Completion rate during treatment was high (81.9%; n = 718), and the incidence of discontinuation owing to adverse events was less than 5% across all treatment groups. Galcanezumab 120-mg and 240-mg monthly injections provided clinical benefits and improved functioning. The incidence rate of adverse events was low, demonstrating the favorable tolerability profile of galcanezumab. ClinicalTrials.gov Identifier: NCT02614183.